Health Technologies Assessment for Orphan Diseases. Example of Social and Economic Burden of Spinal Muscular Atrophy - Aleksei S. Kolbin; Dmitriy V. Vlodavets; Aleksei A. Kurylev; Olga Yu. Germanenko; Natalia Yu. Kolbina (Педиатрическая фармакология)
Background. Studies of the economic impact of disease on society or the social and economic burden, known as developmental disease cost analysis, are equivalent to public health epidemiological studies. Spinal muscular atrophy (SMA) has significant social and economic burden according to various studies.Objective. The aim of the study is to compare Russian and international methodological approaches and results of health technology assessment (HTA) of SMA from the perspective of social and economic burden. Materials and methods. Literature searches were conducted using the Medline, PubMed, ClinicalTrials.gov, and Cochrane Library databases. Keywords and criteria for inclusion and exclusion have been used. The following parameters were used: costs, year of calculation, assessment method, primary and secondary results, type of economic assessment, perspective, time horizon, intervention, analysis of the sensitivity of the results. Both direct medical and non-medical costs were taken into account, as well as indirect costs.Results. The analysis of SMA burden the USA, Germany, Spain, Australia, France, Great Britain, and the Russian Federation was carried out based on 8 international studies and one Russian study that described the costs of SMA. All costs, including indirect ones, were estimated only in 4 international studies and in Russian one. The main source of information was either patient registers or cross-sectional retrospective studies of patients diagnosed with SMA. The costs were higher for type I SMA in all countries. The highest total SMA costs were in the United States, and the lowest in Russian Federation and Spain. Costs excluded new disease-modifying drugs such as nusinersen, risdiplam, and onasemogen abeparvovec in all conducted studies.Conclusions. The social and economic burden of SMA in Russian Federation in 2020 before the introduction of pathogenetic therapy into practice was 2.38 billion RUR/year. The costs of inpatient treatment and rehabilitation were 30.8 and 32.3% of total costs, respectively. These costs, before the introduction of pathogenetic therapy into practice, are lower than in Western Europe and United States, which is most likely since domestic studies used the standards of primary health care for children with SMA implemented in 2012, as well as low indirect costs for SMA in Russian Federation. Unified methodology for assessing the socio-economic significance of orphan diseases is required to carry out HTA of orphan diseases in Russian Federation. It should be based on domestic registries, otherwise on valid data, including those based on data from real clinical practice (RWD /RWE).